Who governs? : democracy and power in an American city - Dahl, Robert A., 1915-2014 (Yale University Press, 1989)
This book is an attempt to throw new light on an ancient question by examining a single American city in New England. Professor Dahl provides a pluralist theory of local power structure. This will become a classic reference for those seeking an understanding of political behavior in modern urban environments under democratic regimes.
Keywords: New Haven (Conn.) -- Politics and government.; Municipal government -- United States -- Case studies.; Community power -- United States -- Case studies.; Administration municipale -- États-Unis -- Études de cas.; Pouvoir communautaire -- États-Unis -- Études de cas.; POLITICAL SCIENCE -- Political Process -- General.; Community power; Municipal government; Politics and government; Connecticut -- New Haven; United States; Case studies; Case studies.; Études de cas.